2020
DOI: 10.1080/13613324.2019.1663912
|View full text |Cite
|
Sign up to set email alerts
|

Male teachers of color: charting a new landscape for educational research

Abstract: The manuscripts in this special issue chart a new landscape for educational research on male teachers of color.The contributors examine the lived complexities subsumed under the umbrella of 'male teachers of color,' and place research on distinct groups of male teachers of color in conversation with one another.The manuscripts in this special issue reflect the diversity and possibility of critical research in education, with an emphasis on the examination of the intersections of social identities for male teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Deconstructing the trope of the urban Black male teacher as "Black Superman" as a potentially debilitating racialized and heteronormative construct of Black masculinity, discussions have also exposed a multitude of reasons why Black men are reluctant to consider teaching and why for those who do enter the profession eventually abandon it (Bristol & Mentor, 2018;Brown et al, 2018;Sleeter, 2017). Black males in particular, may struggle with the thought of becoming teachers given their often highly negative interactions with schools and schooling as K-12 students including low expectations, racial stereotypes, microagressions, and disproportionate discipline and punishment (Goings & Bianco, 2016;Walker, Goings, & Wilkerson, 2019;Woodson & Bristol, 2020). Moreover, low pay, the "de-professionalization" of teaching, a lack of acceptance of Black males outside of secondary, mainstream education, and discriminatory hiring practices further complicate their recruitment into K-12 classrooms (see Bristol & Goings, 2019;D'Amico, Pawlewicz, Earley, & McGeehan, 2017;White, Woodward, Graham, Milner, & Howard, 2019).…”
Section: Black Males and The Choice (Not) To Teachmentioning
confidence: 99%
“…Deconstructing the trope of the urban Black male teacher as "Black Superman" as a potentially debilitating racialized and heteronormative construct of Black masculinity, discussions have also exposed a multitude of reasons why Black men are reluctant to consider teaching and why for those who do enter the profession eventually abandon it (Bristol & Mentor, 2018;Brown et al, 2018;Sleeter, 2017). Black males in particular, may struggle with the thought of becoming teachers given their often highly negative interactions with schools and schooling as K-12 students including low expectations, racial stereotypes, microagressions, and disproportionate discipline and punishment (Goings & Bianco, 2016;Walker, Goings, & Wilkerson, 2019;Woodson & Bristol, 2020). Moreover, low pay, the "de-professionalization" of teaching, a lack of acceptance of Black males outside of secondary, mainstream education, and discriminatory hiring practices further complicate their recruitment into K-12 classrooms (see Bristol & Goings, 2019;D'Amico, Pawlewicz, Earley, & McGeehan, 2017;White, Woodward, Graham, Milner, & Howard, 2019).…”
Section: Black Males and The Choice (Not) To Teachmentioning
confidence: 99%
“…In recent years, there has been an explosion of intervention strategies aimed at increasing the educational achievement of boys of color 1 in schools by providing them with successful role models, mentors, and/or teachers who are also men of color (Brockenbrough, 2018; Harper & Associates, 2014; Jackson et al, 2014; Saenz & Ponjuan, 2011; Woodson & Bristol, 2020). These efforts span educational settings such as K–12 school-day programs, after-school programs, undergraduate university programs, and mentoring programs at the graduate and professional levels.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In particular, BMI programs are able to give young Black men homeplaces on campus, which results in a maximization of sociocultural wealth and an increased sense of belonging. In addition to formalized mentorship programs, MCI and BMI programs on K–12 schools have interlocked with a growing movement to recruit and retain more teachers of color (Achinstein et al, 2010; Villegas & Irvine, 2010) and specifically men of color (Bristol & Goings, 2019; Woodson & Bristol, 2020). This is supported by research that documents the benefits of matching the racial and gender affiliations of teachers and students (Bristol & Martin-Fernandez, 2019).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…While there is a growing body of literature on Black male in-service teachers, the research in this area is scant. In a recent special issue in Race, Ethnicity, and Education (Woodson & Bristol, 2020) that focused on examining burgeoning research on male teachers of color, Young and Young (2020) conducted a 10-year quantitative content analysis on research about Black male teachers. Results from their study suggested that of 31 empirical studies published about Black male teachers from 2006-2016, only three studies (9.7%) focused on preservice teachers, whereas 24 studies (77.4%) were written about the in-service experiences of Black male teachers.…”
Section: Introducing the Special Issuementioning
confidence: 99%